2018
DOI: 10.3389/fphar.2018.01182
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Keap1-Nrf2 Signaling in Mood Disorders: Overview and Future Perspective

Abstract: Depression is one of the most common mood disorders with a high rate of relapse. Accumulating evidence suggests that the transcription factor Kelch-like erythroid cell-derived protein with CNC homology (ECH)-associated protein 1 (Keap1)-Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) system plays a key role in inflammation which is involved in depression. Preclinical studies demonstrated that the protein expressions of Keap1 and Nrf2 in the prefrontal cortex (PFC), CA3 and dentate gyrus (DG) of hippocampus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 106 publications
(159 reference statements)
0
56
0
Order By: Relevance
“…Nuclear factor-E2-related factor 2 (Nrf2) is a transcription factor that binds to antioxidant response elements and has anti-inflammatory effects in addition to anti-oxidative stress[ 16 - 18 ]. There was significantly reduced expression of Nrf2 both in the hippocampus and prefrontal cortex (PFC) of depressive-like mice induced by chronic social defeat stress or stress susceptible rats induced by learned helplessness[ 18 , 19 ].…”
Section: Repetitive Transcranial Magnetic Stimulation Activates the Amentioning
confidence: 99%
“…Nuclear factor-E2-related factor 2 (Nrf2) is a transcription factor that binds to antioxidant response elements and has anti-inflammatory effects in addition to anti-oxidative stress[ 16 - 18 ]. There was significantly reduced expression of Nrf2 both in the hippocampus and prefrontal cortex (PFC) of depressive-like mice induced by chronic social defeat stress or stress susceptible rats induced by learned helplessness[ 18 , 19 ].…”
Section: Repetitive Transcranial Magnetic Stimulation Activates the Amentioning
confidence: 99%
“…(3) Using (3), the R 2 cv is obtained to be 0.554 (Table III). The cross-validated regression coefficient was found to be near to the R 2 value (0.5676) for the best correlation data set and thus this model can be accepted as statistically significant.…”
Section: Cross-validationmentioning
confidence: 99%
“…Glucoraphanin (GF), which found in cruciferous vegetables, such as broccoli sprout, is a glucosinolate precursor of SFN . Previously, we reported that dietary intake of 0.1% GF food pellet could prevent the onset of psychiatric disorders such as depression and psychosis in rodents, suggesting that dietary intake of GF has prophylactic effects for development of psychiatric disorders …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Accumulating evidence suggests that the transcription factor Kelch-like erythroid cell-derived protein with CNC homology (ECH)-associated protein 1 (Keap1)-Nuclear factor (erythroidderived 2)-like 2 (Nrf2) system plays a key role in inflammation which is involved in a number of neurological and psychiatric disorders. [7][8][9][10][11] Multiple lines of evidence suggest a key role of Nrf2 in the pathology of PD. [12][13][14] Jazwa et al 15 reported that sulforaphane (SFN), a potent Nrf2 activator, protects against dopaminergic neurotoxicity in mice after administration of MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine).…”
mentioning
confidence: 99%
See 1 more Smart Citation